Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s13224-014-0548-x
|View full text |Cite
|
Sign up to set email alerts
|

HCV and Pregnancy: Prevalence, Risk Factors, and Pregnancy Outcome in North Indian Population: A Case–Control Study

Abstract: Objectives The study was carried out to investigate the prevalence, risk factors, and Pregnancy outcome in anti-HCV-positives pregnant women admitted for delivery in the Department of Obstetrics & Gynecology of Guru Gobind Singh Medical College and Hospital, Faridkot between January 2010 and January 2013. Setting Department of obstetrics and Gynaecology of GGS Medical College and Hospital, Faridkot. Material and Methods A case-control study design was selected for the study. A total of 1412 pregnant women pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…In contrast to this finding, a study from Faridkot, Punjab reported higher seropositivity among pregnant women belonging to rural areas (72.5%, 29/40) as compared to those from urban areas (27.5%, 11/40). 29 In the present study it was found that majority of pregnant females belonged to lower socio-economic class (68.4%, 376/550), followed by those belonging to middle class (30.0%, 165/550) and least from upper class (1.6%, 9/550). All the 3 reactive females belonged to lower class.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In contrast to this finding, a study from Faridkot, Punjab reported higher seropositivity among pregnant women belonging to rural areas (72.5%, 29/40) as compared to those from urban areas (27.5%, 11/40). 29 In the present study it was found that majority of pregnant females belonged to lower socio-economic class (68.4%, 376/550), followed by those belonging to middle class (30.0%, 165/550) and least from upper class (1.6%, 9/550). All the 3 reactive females belonged to lower class.…”
Section: Discussionsupporting
confidence: 47%
“…28 Similarly, studies from New Delhi and Punjab reported high prevalence of hepatitis C among pregnant women to be 1.03% and 2.8% respectively. 20,29 This 28 Another study from Faridkot, Punjab also reported higher seropositivity among pregnant women belonging to age group 21-25 years (45%, 18/40) and 26-30 years (30%, 12/40). 29 These findings were comparable to the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Anti-HCV prevalence data among pregnant women were available from 15 reports from seven states. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] One study from Chhattisgarh reported a very high seroprevalence rate not only for anti-HCV (7/100; 7.0% [2.86-13.89%]) but also for HBsAg (9/100; 9.0%) and anti-HIV antibodies (12/100; 12%) 14 ; because these rates were quite unusual, this study was excluded from analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A study carried out in Faridkot by Goyal et al 32 screened 1412 pregnant women and found HCV seropositivity in 2.8%. The risk factors to acquire HCV infection identified from this study were a history of previous surgery and blood transfusion.…”
Section: Prevalence Of Hcv Among Pregnant Womenmentioning
confidence: 99%